Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

6y+9-4y=-3
Please solve with work


Sagot :

1)combine like terms
2) move 9 to the other side by subtracting 9
3) divide by the # that is in front of y - to both sides
answer you should get: -11/2
6y+9-4y=-3
6y-4y=2y
2y+9=-3
-9 -9
2y=-12
2/2 -12/2
Y=-6 should be the answer if I did it correctly